Nudges and networks: How to use behavioural economics to improve the life cycle savings-consumption balance - David Blake (Journal of Risk and Financial Management, 2022)
Many people find it difficult to start and maintain a retirement savings plan. We show how nudges can be used both to encourage people to save enough to provide an acceptable standard of living in retirement and to draw down their accumulated pension fund to maximize retirement spending, without the risk of either running out of money or leaving unintended bequests. Networks can help too, particularly employer-based networks. However, the nudges and networks are more likely to be effective if they have legislative backing and support.
Keywords: 650; behavioural economics; life cycle savings-consumption; networks; nudges; Save More Tomorrow (SMART) plans; Spend Optimally Throughout Retirement (SPEEDOMETER) plans